Mental disorders and somatic illnesses - Grzywa, Anna; Makara-Studzińska, Marta; Grzywa-Celińska, Anna (Current Problems of Psychiatry, 2011)
With regard to the growing in popularity concept of holistic approach to man among the representatives of biological science, the tendency to pay attention to various dimensions and multi-causality of somatic diseases has been also present in medicine. The relationship between mental diseases and somatic illnesses can be twofold: in case when somatic factors are crucial in the etiology of mental diseases the term somatogenic mental disease is used, whereas the somatic illness in pathogenesis, where the important meaning is attributed to psychical factors is called the psychosomatic disease. Numerous somatic diseases may influence mental condition of a patient. They include the central nervous system diseases for instance: infections, brain tumors, injuries, degenerative diseases, systemic diseases of other organs directly influencing the central nervous system, such as: infections, endocrinopathies, metabolic disorders, vitamins deficiencies and poisonings. Moreover, nearly always there is a possibility of psychological reaction connected with the very fact of illness development. Mental disorders in somatic illnesses may occur in various forms such as quantitative and qualitative consciousness disorders, mood disorders, delusional syndromes and anxiety syndromes.